Rola Lucjusza Sergiusza Katyliny w wydarzeniach politycznych w Rzymie na przełomie lat 66 i 65 przed Chrystusem - Całus, Katarzyna (Acta Universitatis Lodziensis. Folia Historica, 2015)
Lucius Sergius Catiline was involved in political events in Rome at the turn of 66 and 65. However, it seems doubtful that he was a participant or organizer of the conspiracy to kill Lucius Aurelius Cotta and Lucius Manlius Torquatus. For they were not responsible for the failure of Catiline’s endeavor to hold the office of consul in 65. It appears that it was Cicero who intentionally involved Catiline in the conspiracy to discredit him – his future rival – in the fight for the consulate of 63 year. The name Catilinarian Conspiracy to determine conspiracy aimed at killing the consuls 65 year must, therefore, be regarded as inadequate. Catiline’s actions during the said period must be associated with the accusation de repetundis of Gaius Manilius – the tribune of the people. Organizing the militias, Catiline himself did not want to be brought before the court, hoping that thanks to the intercession of Pompey he will avoid the conviction during his trial for extortion in the provinces.